1987
DOI: 10.1139/y87-364
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-adrenergic agonist infusions on myometrial activity and plasma prostaglandin levels in the nonpregnant sheep

Abstract: Recent studies have reported that beta-adrenergic agonists stimulate the production of stimulatory prostaglandins (PGs) by intrauterine tissues in vitro. These drugs are used clinically to inhibit uterine contractions; consequently an increase in stimulatory PGs in vivo might have potentially adverse effects. We have, therefore, investigated whether beta-adrenergic agonists increase plasma PG concentrations in vivo. Samples of peripheral (aorta) and uterine venous enriched (vena cava) blood from nonpregnant sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1990
1990
1994
1994

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In contrast, we found that de sensitization was associated with a significant re duction in the number (but not affinity) of β-adren ergic receptors. 41 We have observed similar examples of homolo gous myometrial desensitization to β-adrenergic agonists in vivo in rats 43 as well as nonpregnant 44 and pregnant sheep. 45 In the latter study preterm labor was induced in sheep by injection of the pro gesterone receptor antagonist, RU486.…”
Section: Homologous Desensitizationsupporting
confidence: 52%
See 1 more Smart Citation
“…In contrast, we found that de sensitization was associated with a significant re duction in the number (but not affinity) of β-adren ergic receptors. 41 We have observed similar examples of homolo gous myometrial desensitization to β-adrenergic agonists in vivo in rats 43 as well as nonpregnant 44 and pregnant sheep. 45 In the latter study preterm labor was induced in sheep by injection of the pro gesterone receptor antagonist, RU486.…”
Section: Homologous Desensitizationsupporting
confidence: 52%
“…22 Similarly, Casper and Lye found that intermittent administration of the short-acting β-adrenergic agonist isoproterenol pre vents the onset of myometrial desensitization in nonpregnant sheep. 44 Spalting and colleagues 52 have reported greater prolongation of pregnancy and in creased birth weights with intermittent pulses of fenoterol, as compared to continuous infusion. Other studies have suggested that agents other than betamimetics be used to initially arrest uterine contrac tions followed by a continuous basal infusion of terbutaline accompanied with intermittent boluses of this drug.…”
Section: Increased Efficacy Of β-Adrenergic Agonists: Intermittent Agmentioning
confidence: 99%